Success and failures of telehealth during COVID‐19 should inform digital applications to combat obesity - Joseph R. Vasselli; Susan Juray; Steven E. Trasino (Wiley, 2022)
Abstract Background In response to the COVID‐19 pandemic, telehealth digital applications (apps) permitted the delivery of health care to millions of individuals, including those with poor access to health services. Aim To review a body of evidence demonstrating that telehealth and mobile health (mHealth) apps can promote clinically meaningful weight loss, and thus hold potential to increase access to treatment and weight loss care for individuals suffering from obesity. Results Data from COVID‐19 pandemic revealed that access to telehealth and mHealth remains a challenge for underserved communities that are disproportionately affected by obesity. Conclusions The development of telehealth and mHealth for obesity treatment must be informed by the success and failures of telehealth during the COVID‐19 pandemic. Failure to do so, risks alienating the very populations that stand most to benefit from telehealth and mHealth apps for obesity treatment.